Coherent coupling and optical manipulation of individual excitonic states - Patton, B; Woggon, U; Langbein, W (2005)
We present heterodyne detected transient four-wave mixing of individual exciton states. Coherent coupling between states is observed and single excitons are optically manipulated, driving their polarisation through a desired angle in the Bloch sphere. © 2004 Optical Society of America.